Concomitant intramyocardial and hepatic hydatid cysts diagnosed by multi-modality imaging: A rare case report - Nguyen, Hoai Thi Thu; Pham, Viet Tuan; Duong, Hung Duc; Kirkpatrick, James N.; Taylor, Walter Robert; Pham, Hung Manh (Frontiers in Cardiovascular Medicine, 2022)
Cardiac echinococcosis is a potentially fatal form of hydatid disease; yet, its diagnosis and treatment are challenging due to the variability in its clinical manifestations and due to its various unpredictable preoperative complications. Multi-modality imaging is shown to provide important guidance for the treatment and decision-making. We report a rare case of a 50-year-old woman who had concomitant cardiac and hepatic hydatid cysts. She presented with abdominal pain and elevated eosinophilic white blood cells. The initial abdominal ultrasound and computerized tomography revealed a large cyst in the liver. An intramyocardial cyst was detected by two-dimensional echocardiography. Three-dimensional echocardiography increased the confidence level of two-dimensional echocardiography by displaying the three-dimensional volume of the cyst and allowing visualization of its spatial characteristics and the relationships with adjacent cardiac structures, which was subsequently confirmed at surgery. Multi-detector computed tomography and magnetic resonance imaging helped localize and define the typical morphological features of the cyst. Serology and antigen detection were used for diagnosis. This rare case underlines the integration of clinical, multi-modality imaging, and pathological data in the diagnosis of concomitant intramyocardial and hepatic hydatid cysts. Surgical resection of cysts and anthelmintic medication were successful in the management of this patient.